Effect of seed sludge on nitrogen removal in a novel upflow microaerobic sludge reactor for treating piggery wastewater. (September 2016) - Meng, Jia; Li, Jiuling; Li, Jianzheng; Wang, Cheng; Deng, Kaiwen; Sun, Kai
Highlights: Two upflow microaerobic sludge reactors were constructed to treat MFPW. Aerobic and anaerobic activated sludge (S) were the inocula, respectively. Aerobic S was easier being accumulated than anaerobic S, only feasible for low NLR. The accumulated anaerobic AS was feasible for treating MFPW with higher NLR. An increased loading rate changed microbial community structure and removal load. Abstract: Anaerobic activated sludge (AnaS) and aerobic activated sludge (AerS) were used to start up a novel upflow microaerobic sludge reactor (UMSR), respectively, and the nitrogen removal in the two reactors were evaluated when treating low C/N ratio manure-free piggery wastewater with a COD/TN ration of about 0.85. With the same hydraulic retention time 8 h and TN loading rate (NLR) 0.42 kg/(m 3 d), the UMSR (R2) inoculated with AerS could reach its steady state earlier and obtained a better TN removal than that in the UMSR (R1) inoculated with AnaS. However, the accumulated AnaS made R1 show a better capability in bearing shock load and demonstrated an excellent NH4 + -N and TN removal with a NLR as high as 1.07 kg/(m 3 d). Microbial community structure of the accumulated AerS and AnaS were observable different. The decreased proportion of nitrifiers restricted the ammonium oxidation in R2, and resulting in a decrease in TN removal.